TRPC1/4/5 channels contribute to morphine‐induced analgesic tolerance and hyperalgesia by enhancing spinal synaptic potentiation and structural plasticity. Issue 6 (2nd May 2020) - Chu, Wen‐Guang; Wang, Fu‐Dong; Sun, Zhi‐Chuan; Ma, Sui‐Bin; Wang, Xu; Han, Wen‐Juan; Wang, Fei; Bai, Zhan‐Tao; Wu, Sheng‐Xi; Freichel, Marc; Xie, Rou‐Gang; Luo, Ceng
Abstract: Opioid analgesics remain the mainstay for managing intractable chronic pain, but their use is limited by detrimental side effects such as analgesic tolerance and hyperalgesia. Calcium‐dependent synaptic plasticity is a key determinant in opiates tolerance and hyperalgesia. However, the exact substrates for this calcium‐dependent synaptic plasticity in mediating these maladaptive processes are largely unknown. Canonical transient receptor potential 1, 4, and 5 (TRPC1, 4, 5) proteins assemble into heteromultimeric nonselective cation channels with high Ca 2+ permeability and influence various neuronal functions. However, whether and how TRPC1/4/5 channels contribute to the development of opiates tolerance and hyperalgesia remains elusive. Here, we show that TRPC1/4/5 channels contribute to the generation of morphine tolerance and hyperalgesia. Chronic morphine exposure leads to upregulation of TRPC1/4/5 channels in the spinal cord. Spinally expressed TRPC1, TPRC4, and TRPC5 are required for chronic morphine‐induced synaptic long‐term potentiation (LTP) as well as remodeling of synaptic spines in the dorsal horn, thereby orchestrating functional and structural plasticity during the course of morphine‐induced hyperalgesia and tolerance. These effects are attributed to TRPC1/4/5‐mediated Ca 2+ elevation in the spinal dorsal horn induced by chronic morphine treatment. This study identifies TRPC1/4/5 channels as a promising novel target to prevent the unwanted morphine tolerance and hyperalgesia.